PENGARUH KETINGGIAN FERROTRAP TERHADAP JUMLAH KUMBANG TANDUK (Oryctes rhinoceros Linneus.) YANG TERTANGKAP DI PERKEBUNAN KELAPA SAWIT - Andi Widodo; Ahmad Saleh; Sulthon Parinduri (Institut Teknologi Sawit Indonesia, 2018)
Oryctes rhinoceros is an important pest of oil palm that cause considerable losses and attack oil palm plants across Indonesia. The damage of beetle attacks can occur in immature plants, as well as the mature plants. The losses caused by these beetles is quite large because the beetles bore into the crown which can e ect to the broken stem. The research was conducted in Afdeling II Kebun Adolina PT. Perusahaan Nusantara IV, Serdang Bedagai Regency, North Sumatra Province on 11 – 27 August 2017. Research method used by traps the beetle using pheromone against the lengthof stick of the trap with four repetitions that are placed in immature plants. The conclusion from this research that the 2 meters of stick ferotrap length traps more Oryctes rhinoceros compared to 4 meters of stick ferotrap length. The large number of pheromones in traps do not a ect the interest of Oryctes rhinoceros.